Salvage logging in the world's forests: Interactions between natural disturbance and logging need recognition - Leverkus, Alexandro B.; Lindenmayer, David B.; Thorn, Simon; Gustafsson, Lena (Global ecology and biogeography, 2018)
Aim: Large disturbances increasingly shape the world's forests. Concomitantly, increasing amounts of forest are subject to salvage logging. Understanding and managing the world's forests thus increasingly hinges upon understanding the combined effects of natural disturbance and logging disturbance, including interactions so far unnoticed. Here, we use recent advances in disturbance-interaction theory to disentangle and describe the mechanisms through which natural disturbance (e.g., wildfire, insect outbreak or windstorm) can interact with anthropogenic disturbance (logging) to produce unanticipated effects. We also explore to what extent such interactions have been addressed in empirical research globally. Insights: First, many ecological responses to salvage logging likely result from interaction modifications—i.e., from non-additive effects–between natural disturbance and logging. However, based on a systematic review encompassing 209 relevant papers, we found that interaction modifications have been largely neglected. Second, salvage logging constitutes an interaction chain because natural disturbances increase the likelihood, intensity and extent of subsequent logging disturbance due to complex socio-ecological interactions. Both interaction modifications and interaction chains can be driven by nonlinear responses to the severity of each disturbance. We show that, whereas many of the effects of salvage logging likely arise from the multiple kinds of disturbance interactions between natural disturbance and logging, they have mostly been overlooked in research to date. Conclusions: Interactions between natural disturbance and logging imply that increasing disturbances will produce even more disturbance, and with unknown characteristics and consequences. Disentangling the pathways producing disturbance interactions is thus crucial to guide management and policy regarding naturally disturbed forests.